FAKTOR PENENTU KESIAPAN KERJA MAHASISWA DEPARTEMEN STATISTIKA BISNIS ITS - Purwono, M. Djoko; Kustiningsih, Nanik; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to evaluate the influence of gender, academic performance, organizational activity and soft skills on student work readiness at the Department of Business Statistics, Institut Teknologi Sepuluh Nopember (ITS). This study also examines the simultaneous influence of the four variables. A quantitative method based on historical data was used involving 93 seventh-semester students (25 male students and 68 female students) who were selected using the total sampling method. Data was collected through questionnaires and supporting documents, then analyzed by multiple linear regression using SPSS version 23. The results of the analysis showed that gender, academic performance, organizational involvement, and soft skills simultaneously and partially had a significant effect on student’s job readiness. These findings emphasize the importance of developing technical and non-technical skills in preparing students for the world of work.